The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5539/ijms.v5n4p110
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurial Marketing and Business Development on Business Sustainability: Small and Household Footwear Industries in Indonesia

Abstract: Entrepreneurial marketing is a marketing approach that is more appropriate in terms of resource constraints and problems that exist in small and medium enterprises (SMEs). Although the footwear industry is one of the government-supported SMEs sector in Indonesia, the development of the industry is still relatively slow. Various government policies have been implemented related to export and import settings, but it does not seem to provide significant benefits to the national development of the footwear industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 4 publications
1
8
0
9
Order By: Relevance
“…Different studies have shown that various elements of entrepreneurial marketing have significant positive impact on organizational performance (Hacioglu, Even, Even & Celikkan, 2012;Hamali, 2015;Ma, Kim, Heo & Jang, 2012;Mwangi & Bwisa, 2013;Sarma, Septiani, Dewi & Siregar, 2013). In today's competitive world, the survival of organizations depends on innovation, creativity and entrepreneurship (SaeediKia, 2007) and those firms with a stronger entrepreneurial orientation have better performance than their counterparts in the same industry (Moghimi & Ahmadpour, 2007).…”
Section: Organizational Performance Influencing Factorsmentioning
confidence: 99%
“…Different studies have shown that various elements of entrepreneurial marketing have significant positive impact on organizational performance (Hacioglu, Even, Even & Celikkan, 2012;Hamali, 2015;Ma, Kim, Heo & Jang, 2012;Mwangi & Bwisa, 2013;Sarma, Septiani, Dewi & Siregar, 2013). In today's competitive world, the survival of organizations depends on innovation, creativity and entrepreneurship (SaeediKia, 2007) and those firms with a stronger entrepreneurial orientation have better performance than their counterparts in the same industry (Moghimi & Ahmadpour, 2007).…”
Section: Organizational Performance Influencing Factorsmentioning
confidence: 99%
“…Niammuad et al(2014), melakukan kajian tentang kewirausahaan yang dikaitkan dengan inovasi produk dalam upaya meningkatkan daya saing. Sarma et al,(2013) dan Septiani et al,(2013) memadukan antara EM dengan daya saing. Penelitian daya saing dilakukan pula oleh Singh dan Sirdeshmukh,(2000) yang menemukan kepercayaan merupakan dasar dalam membangun dan memelihara hubungan jangka panjang.…”
Section: Pendahuluanunclassified
“…Kemudian penelitian yang dilakukan Kocak dan Abimbola (2009), Thomas et al(2013), serta Mort et al (2012) menyatakan bahwa EM yang salah satu dimensinya mengembangkan inovasi perusahaan, di mana dengan adanya inovasi akan menghasilkan keunggulan produk sehingga mampu meningkatkan daya saing dalam lingkungan pasar global yang sangat kompetitif (Cooper, 2000). Sarma et al (2013) menyatakan bahwa EM penting bagi perusahaan agar dapat memiliki daya saing sehingga mampu bertahan dan tumbuh dalam persaingan global yang semakin ketat dewasa ini. Demikian juga senada dengan pendapat Kurgun et al (2011) yang menyatakan EM mempengaruhi daya saing setelah perusahaan melakukan perubahan dalam produk dan layanan.…”
Section: Pendahuluanunclassified
“…They also lack the ability to compete in the challenging market environment. Although, there are various policies and supports given by the government to help small businesses boost their sales locally and abroad, the development of the small businesses are still slow (Sarma, Septiani, Dewi, & Siregar, 2013).…”
Section: Problem Statementmentioning
confidence: 99%